2016
DOI: 10.1016/j.molp.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Regulatory DNA Elements Using Genome-wide Mapping of DNase I Hypersensitive Sites during Tomato Fruit Development

Abstract: Development and ripening of tomato fruit are precisely controlled by transcriptional regulation, which depends on the orchestrated accessibility of regulatory proteins to promoters and other cis-regulatory DNA elements. This accessibility and its effect on gene expression play a major role in defining the developmental process. To understand the regulatory mechanism and functional elements modulating morphological and anatomical changes during fruit development, we generated genome-wide high-resolution maps of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 72 publications
5
32
1
Order By: Relevance
“…Overall, the identified accessible regions were mostly enriched around the TSSs (Fig. 1D), which is consistent with the fact that these regions usually contain active regulatory cis- elements (Qiu et al 2016). The signal intensity of accessible regions became weaker as the distance from the TSS became greater in both the Watson and Crick strands (Fig.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Overall, the identified accessible regions were mostly enriched around the TSSs (Fig. 1D), which is consistent with the fact that these regions usually contain active regulatory cis- elements (Qiu et al 2016). The signal intensity of accessible regions became weaker as the distance from the TSS became greater in both the Watson and Crick strands (Fig.…”
Section: Resultssupporting
confidence: 82%
“…The chromatin accessibility regions of A. niger CBS513.88 and SH2 were similarly distributed across the various elements of the genome; the chromatin accessibility regions were found in a high proportion at TSSs (∼70%) and in a low proportion at intergenic regions (∼5%). The proportional distribution of accessible regions is different from what is observed in humans (Ackermann et al 2016), Arabidopsis (Tannenbaum et al 2018) and tomato (Qiu et al 2016), which show a high distribution in intergenic regions and gene bodies. This difference may reflect the smaller size of the A. niger genome (35 Mb) compared with the larger and less compact genomes of humans (750 Mb), Arabidopsis (125 Mb) and tomato (900 Mb).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…These technologies were successfully applied to identify functional CREs in several model animal species, including humans (The ENCODE Project Consortium, 2004), mouse (Stamatoyannopoulos et al, 2012), Caenorhabditis elegans, and Drosophila melanogaster (Hesselberth et al, 2009;Gerstein et al, 2010). Similar efforts have recently been reported in plants (Zhang et al, 2012a;Zhang et al, 2012b;Pajoro et al, 2014;Sullivan et al, 2014;Cumbie et al, 2015;Qiu et al, 2016), which showed that open chromatin possesses unique epigenetic modifications (Zhang et al, 2012a) and is associated with DNA sequences bound to transcription factors (TFs; Zhang et al, 2012b) and with enhancer function (Zhu et al, 2015). These studies provided insights on the regulatory landscape and transcription factor networks in plant species.…”
mentioning
confidence: 89%